Morphology and Immunophenotypes of Canine Lymphomas: a Survey from the Service of Animal Pathology, School of Veterinary Medicine and Animal Science, University of São Paulo, Brazil - Kimura, Kátia C.; Zanini, Danielle A.; Nishiya, Adriana T.; Dias, Ricardo A.; Dagli, Maria L. Z. (Brazilian Journal of Veterinary Pathology, 2011)
Lymphoma is a malignant clonal expansion of lymphoid cells, and is reported to be one of the most common hematopoietic neoplasms in dogs. The purpose of this study was to perform a survey of lymphomas diagnosed at the Service of Animal Pathology of the School of Veterinary Medicine and Animal Science, University of São Paulo, Brazil, from 1995 to 2009, and determine their morphological subtypes and immunophenotypes. Breed, age and gender were recorded. The canine lymphomas were classified according to the updated Kiel classification, and all the cases were submitted to immunostaining for CD3 and CD79a antibodies to reveal their T or B origin, respectively. In addition, mitotic figures were counted in all samples, in 10 microscopic fields. Mixed breed dogs were the most affected breed (43%), followed by Boxer (14%), German Shepherd (11%), Brazilian terrier (3%), Poodle (3%) and Rottweiler (3%). Other breeds were represented at a rate below 1%. Among the 65 cases of lymphomas, 30 cases were found in females and 35 in males. The mean age was 8.7 years with a range of 5 months to 15 years. The most frequent localization was multicentric lymphadenopathy (37%), followed by extranodal (23%), cutaneous (20%), alimentary tract (18%) and mediastinal site (2%). From 65 canine lymphomas, 55 (85%) had T-cell origin and 10 (15%) had B-cell origin. Among mitotic index, 51% (n=33) of T-cell origin had high mitotic index, 34% (n=22) had a low mitotic index; 9% (n=6) of B-cell origin had high mitotic index and 6% (n=4) had low mitotic index. The most common subtypes were pleomorphic small cell and centroblastic polymorphic type for T-cell lymphoma and B-cell lymphoma, respectively. The 55 T-cell lymphomas were subtyped as: 19 (34%) of pleomorphic small cell, 11 (20%) of cutaneous T cell, high grade, 10 (18%) of lymphoblastic, 4 (7%) of aggressive large granular cell, 3 (5%) of pleomorphic mixed, 2 (4%) of cutaneous T cell, low grade, 2 (4%) of pleomorphic large cell, 2 (4%) of plasmacytoid, 1 (2%) of immunoblastic and 1 (2%) of prolymphocytic. The 10 B-cell lymphomas were subtyped as: 3 (30%) of centroblastic polymorphic, 2 (20%) of Burkitt, 2 (20%) of lymphoplasmacytic, 1 (10%) of anaplastic/mediastinal, 1 (10%) of small lymphocytic and 1 (10%) of prolymphocytic. Our results are in accordance with other studies which state that T-cell lymphomas are the most common in dogs. The possible factors that contribute to the development of lymphomas in dogs remain unknown.